PENGENDALIAN MUTU CILOK AYAM DENGAN CHECKSHEET, DIAGRAM PARETO, DAN DIAGRAM FISHBONE PADA USAHA CILOK GURILEM DI SUKABUMI: Indonesia - Suhendar, Aulia; Putra, Made Bintang Prabaswara; Nurwahda, Nizma Afrah; Ghalib, Abdul; Auliaurrahman, Hasya (Agripreneur : Jurnal Pertanian Agribisnis, 2025)
This study aims to analyze product quality at the Cilok Ayam Gurilem Sukabumi business using three simple problem-solving tools, namely checksheets, Pareto diagrams, and fishbone diagrams. These three tools are used to map the types of defects that arise during the production process and identify the dominant contributing factors. Data collection was conducted through direct observation and daily recording over a period of four weeks, thereby obtaining a realistic picture of product quality variations. The results of the study show that shape defects were the most dominant problem with a total of 3,058 units (54%), followed by raw material inconsistencies amounting to 1,900 units (34%), and thin dough at 680 units (12%). Through a fishbone diagram, the main causes were identified as unstandardized forming techniques, varying raw material quality, and equipment conditions requiring better maintenance. Implicitly, this research provides practical contributions to food MSMEs in the form of a simplequality control model that can be directly applied without significant costs, while also providing added value in the form of an integrative approach between quantitative and qualitative data to trace the root causes of production problems. Overall, this study emphasizes the importance of implementing work standards, operator training, and more systematic raw material inspections to improve quality consistency and production sustainability.